RANCANGAN TATA KELOLA SERVICE DESK BERBASIS INFORMATION TECHNOLOGY INFRASTRUCTURE LIBRARY VERSION 3 - STUDI KASUS PADA HASNUR GROUP - Yulianingsih Yulianingsih; Dana Indra Sensuse (LPPM, 2011)
A successful Implementation of IT has been transformiting the company while creating value added products and services has been a universal business competition. To enable a well targeted implementation of services governance it is well known that a respectable best practice guidance is required. One of a recognized framework is Information Technology Infrastructure Libraryv (ITIL). In this research, to represent current IT service activity condition, a maturity level assessment has been conducted according to process areas. Maturity level assessment result compared with high level management expectation introduced as gap analysis. The given solution to overcome the gap compiled referred to ITIL. Key Words: Governance, Information Technology Infrastructure Library, maturity, assessment, gap analysis.